On a Class of Meromorphic Multiivalent Functiions Convoluted withi Higher Derivatiives of Fractionali Calculus Operator - Jassim, Kassim Abdul Hameed; Hussein, Sattar Kamil (Iraqi Journal of Science, 2019)
The main goal of this paper is to study and discuss a new class of meromorphici "functions[ which are multivalent defined by [fractional calculus operators. Coefficients iestimates , radiisi of satarlikeness , convexityi and closed-to-iconvexity are studied. Also distortion iand closure theorems for the classi" , are considered.